European trends in epilepsy surgery. (10th July 2018) - Baud, Maxime O.; Perneger, Thomas; Rácz, Attila; Pensel, Max C.; Elger, Christian; Rydenhag, Bertil; Malmgren, Kristina; Cross, J. Helen; McKenna, Grainne; Tisdall, Martin; Lamberink, Herm J.; Rheims, Sylvain; et al.
Abstract : Objective: Resective surgery is effective in treating drug-resistant focal epilepsy, but it remains unclear whether improved diagnostics influence postsurgical outcomes. Here, we compared practice and outcomes over 2 periods 15 years apart. Methods: Sixteen European centers retrospectively identified 2 cohorts of children and adults who underwent epilepsy surgery in the period of 1997 to 1998 (n = 562) or 2012 to 2013 (n = 736). Data collected included patient (sex, age) and disease (duration, localization and diagnosis) characteristics, type of surgery, histopathology, Engel postsurgical outcome, and complications, as well as imaging and electrophysiologic tests performed for each case. Postsurgical outcome predictors were included in a multivariate logistic regression to assess the strength of date of surgery as an independent predictor. Results: Over time, the number of operated cases per center increased from a median of 31 to 50 per 2-year period ( p = 0.02). Mean disease duration at surgery decreased by 5.2 years ( p < 0.001). Overall seizure freedom (Engel class 1) increased from 66.7% to 70.9% (adjusted p = 0.04), despite an increase in complex surgeries (extratemporal and/or MRI negative). Surgeries performed during the later period were 1.34 times (adjusted odds ratio; 95% confidence interval 1.02–1.77) more likely to yield a favorable outcome (Engel class I) than earlier surgeries, and improvement was more marked in extratemporal and MRI-negative temporal epilepsy. The rate of persistent neurologic complications remained stable (4.6%–5.3%, p = 0.7). Conclusion: Improvements in European epilepsy surgery over time are modest but significant, including higher surgical volume, shorter disease duration, and improved postsurgical seizure outcomes. Early referral for evaluation is required to continue on this encouraging trend.